Performance of monetary policy with internal central bank forecasting - Seppo Honkapohja; Kaushik Mitra (Bank of Finland, 2002)
Recent models of monetary policy have analysed the desirability of different optimal and ad hoc interest-rate rules under the restrictive assumption that forecasts of the private sector and central bank are homogeneous.In this paper, we study from a learning perspective the implications of heterogeneity across forecasts by the central bank and private agents for the performance of interest-rate rules.
URN:NBN:fi:bof-20140807525
Keywords: E52; E31; D84; 330; adaptive learning; stability; heterogeneity; monetary policy